Hypergraph Theory An Introduction - Bretto, Alain; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
This authored monograph presents hypergraph theory and covers both traditional elements of the theory as well as more original concepts such as entropy of hypergraph, similarities and kernels. Moreover, the author gives a detailed account to applications of the theory, including, but not limited to, applications for telecommunications and modeling of parallel data structures. The target audience primarily comprises researchers and practitioners in applied sciences but the book may also be beneficial for graduate students.
Hypergraphs: basic concepts -- Hypergraphs: first properties -- Hypergraph coloring -- Some particular hypergraphs -- Reduction-contraction of Hypergraph -- Dirhypergraphs: basic concepts -- Applications of hypergraph theory : a brief overview.
Keywords: Mathematics; Computer science -- Mathematics; Algorithms; Graph theory; Applied mathematics; Engineering mathematics; Electrical engineering; Mathematics; Graph Theory; Discrete Mathematics in Computer Science; Communications Engineering, Networks; Appl.Mathematics/Computational Methods of Engineering; Algorithms; Electronic books